3D-analysis of unwanted tooth movements despite bonded orthodontic retainers: a pilot study - Katharina Klaus; Faidra Xirouchaki; Sabine Ruf (BMC, 2020)
Abstract Background Recently, reports of unwanted tooth movements despite intact orthodontic bonded retainers have increased. These movements are not subject to relapse but are classified as a new developed malocclusion. The aims of the present pilot study were to analyze the prevalence of unwanted tooth movements despite intact bonded cuspid-to-cuspid retainers and to identify possible predisposing factors. Materials and methods Plaster casts of all patients finishing orthodontic treatment during three consecutive years were assessed before treatment (T0), after multibracket appliance debonding (T1) and after two years of retention (T2). After multibracket appliance treatment, all patients received a cuspid-to-cuspid flexible spiral wire retainer bonded to each tooth of the retained segment in the upper and lower jaw. The study group (SG) consisted of 44 patients (16 male, 28 female) with tooth movements (T1-T2) of the retained segment despite intact bonded cuspid-to-cuspid retainer and the control group (CG) of 43 patients (19 male, 24 female) without unwanted tooth movements. The casts of the SG were digitized, superimposed and measured. Using the Chi-square test, Fisher´s exact test and Mann-Whitney-U-test (p < 0.05), mandibular plane angle, incisor proclination, oral dysfunctions or habits (T0) and intercanine distance, overjet and interincisal relationship (T0, T1, T2) were compared between SG and CG. Results The prevalence of patients with unwanted tooth movements in one or both jaws was 27.0%. Maxillary retainers were affected more often (20.9%) than mandibular retainers (14.1%). The median amount of tooth movements was 0 to 0.66 mm with large interindividual variations. Oral dysfunctions or habits at T0, such as a lack of interincisal contact at all time points, were associated with unwanted tooth movements. Conclusion Unwanted tooth movements occurred more often with maxillary than mandibular retainers. Patients with oral dysfunctions/habits and without interincisal contact had a higher prevalence of unwanted tooth movements.